From Minority to Maturity: The Evolution of Later Lollardy - Stansfield-Cudworth, R. E. (Socio-historical examination of religion and ministry, 2021)
Though English supporters of the Oxford theologian John Wycliffe (d.1384)—known as "Lollards"—had been drawn from academic and noble/gentry circles during the later-fourteenth and early-fifteenth centuries, persecution, equation of heresy with sedition, and the failure of Sir John Oldcastle’s Rebellion (1414) ensured overt abandonment of Lollard ideas. Consequently, post-1414 ("later") Lollardy in England has been characterized as an amorphous, introverted network—appealing to those of lesser socio-economic status—being unworthy of description as a sect because of its deficiency of organization. However, the movement’s consistency and infrastructure are reappraised by considering its heterogeneity in terms of society (demography, literacy, and socio-economic status), interactions (modes of dissemination), and motivation, participation, and organization (appreciating the dynamics of religious movements). From a comparative perspective, Lollardy’s acephalous, reticulate infrastructure—similarly to that of Waldensianism and other movements—may have proved beneficial by facilitating adaptability during persecution thereby ensuring Lollardy’s survival until the Reformation.